The Temporal Modulation of Nocebo Hyperalgesia in a Model of Sustained Pain - Camerone, Eleonora Maria; Battista, Simone; Benedetti, Fabrizio; Carlino, Elisa; Sansone, Lucia Grazia; Buzzatti, Luca; Scafoglieri, Aldo; Testa, Marco (Frontiers in Psychiatry, 2022)
Background. The direction and the magnitude of verbal suggestions have been shown to be strong modulators of nocebo hyperalgesia, while little attention has been given to the role of their temporal content. Here, we investigate whether temporal suggestions modulate the timing of nocebo hyperalgesia in an experimental model of sustained pain. Methods. Fifty-one healthy participants were allocated to one of three groups. Participants received an inert cream and were instructed that the agent had either hyperalgesic properties setting in after 5 (Nocebo 5, N5) and 30 (Nocebo 30, N30) minutes from cream application, or hydrating properties (No Expectation Group, NE). Pain was induced by the Cold Pressure Test (CPT) which was repeated before cream application (baseline) and after 10 (Test10) and 35 (Test35) minutes. Changes in pain tolerance and in HR at each test point in respect to baseline were compared between the three groups. Results. Tolerance change at Test 10 (Δ10 ) was greater in N5 (MED=-36.8;IQR=20.9) compared to NE (MED=-5.3;IQR=22.4;p<.001) and N30 (MED=0.0;IQR=23.1;p<.001), showing that hyperalgesia was only present in the group that expected the effect of the cream to set in early. Tolerance change at Test 35 (Δ35 ) was greater in N5 (MED=-36.3;IQR=35.3; p=.002) and in N30 (MED=-33.3;IQR=34.8;p=.009) compared to NE, indicating delayed onset of hyperalgesia in N30, and sustained hyperalgesia in N5. No group differences were found for HR. Conclusions. Our study demonstrated that temporal expectations shift nocebo response onset in a model of sustained pain.